The administrative judiciary reforms in Lithuania - Paužaitė-Kulvinskienė, Jurgita (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
<p class="abstrakt" style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The study concerns the reforms of the administrative judiciary in Lithuania, starting from the interwar period, and the importance of prof. Mykolas Römeris, to modern times. The Lithuanian model of legal protection against actions of public administration is based on Art. 111 sec. 2 of the Lithuanian Constitution, which provides for the possibility of establishing specialized courts to hear administrative cases. Since 2001, this judiciary has two instances: it consists of district administrative courts as courts of first instance and the Supreme Administrative Court. It is part of the judicial system but is separate from the common and constitutional courts. <p class="abstrakt" style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The Lithuanian administrative judiciary is now considered to be very modern, taking into account progressive European trends. Its characteristic feature are, among others extensive forms of alternative settlement of public law disputes, such as pre-trial proceedings, settlement or mediation. The Lithuanian legislator, however, continues efforts to modernize it further. The subject of the current discussion is the reform of the appeal procedure, assuming an increase in the effectiveness of this procedure by introducing a filtering mechanism for complaints brought to the court of second instance.